Os eventos geográficos e a expansão urbana de Caicó: desigualdades e coexistências na URBE - Faria, Carlos Eugenio de (2010)
This research arose from the interest on the investigation about urban expansion from Caicó. Since its creation as a village and its ascent to the condition of city, but especially , the occurred expansion from the 70s, when the local cotton economy begins to present signs of exhaustion. The central theme of this work consists on the importance of the geographical events and its relations with the phenomenon of the urban expansion from Caicó that served us as empirical basis. In relation to the events, that appear as elements of analysis on the works from the Professor Milton Santos, especially on the book Nature of Space , they appear as a kind of urban extensors energizing the areas where are installed. Understood by us as a vehicle of one or more possibilities, according to Santos, (1999) we listed some events occurred in the caicoense urbs a nd we divided them into principal and derivative ones, such events implemented from their structures, forms and functions, through processes that resulted and still continue to result the enlargement of the caicoense urban perimeter , densifications enough important for this urban expansion. The technical periods of cattle raising , cotton, as well as the tertiary city and its connections with the role of fast men, as well as slow men is also important aspect in the body of this work. It is still pointed out the inequalities and the coexistences that are generated on the basis of these connections and finally we discussed the positive and negative consequences elapsed from the phenomenon of the urban expansion